Active breaks programme in classroom planning in schools of The Life Skills Programme in The Lagos region - Cárcamo Saldías, Ángelo Rodrigo (2022)
With a quasi-experimental design, a population of 114 teachers of the first basic cycle of the life skills programme, the non-probabilistic sample made up of a control group and an experimental group of 30 teachers, a checklist was applied, validated by experts, and a pilot test, with a reliability of 0.89 from KR20. By the Shapiro-Wilk test, a normal distribution of data was determined. Concluding: The test test on classroom planning, the value of p=.000 is obtained, that this value is smaller than the expected critical 0.05, approving the alternative hypothesis the program of active breaks influences in the planning of classrooms in schools attached to the program skills for life region of Los Lagos, Chile 2021, the statistical analysis of the test of the post test on classroom planning in the dimension of classroom planning and performance in the control and experimental group, the value of p=0.00 is obtained, this value is smaller than the expected critical 0.05.